Severe Leukemic Retinopathy due to Acute Lymphoblastic leukemia - Hossain, Ireen; Rahman, Niaz Abdur; Kadir, Syeed Mehbub Ul (Community Based Medical Journal, 2024)
Leukaemia is a myeloproliferative disorder which commonly affects the eye. The retina is most commonly affected by leukaemia. Both acute and chronic leukaemia can develop retinopathy. Patients can develop anaemia and thrombocytopenia. The ophthalmic features include white-centred retinal haemorrhages (Roth spot), cotton wool spots, macular haemorrhages and vitreous haemorrhages. CNS involvement through the optic nerve can cause papillo-oedema and cranial nerve palsy. Opportunistic infection can occur after chemotherapy. A young female patient was diagnosed with Acute Lymphoblastic leukaemia (ALL); she presented with pain and blurred vision in both her eyes. In coloured fundus photograph (CFP) shows dilated, tortuous blood vessels and grey-white streaks along vessels due to perivascular infiltrate. Large whitish opacity all over the fundus. Optic nerve infiltration is also present. Vascular occlusion like CRVO occurs due to hyperviscosity. OCT shows leukaemic infiltration of the retina, causing detachment. The modalities of the Management of leukaemia involve chemotherapy, immunotherapy or radiotherapy, but the Management of leukaemic retinopathy is symptomatic. ALL is treated with vincristine, prednisolone and L-asparagine. Eye treatment was done by intravitreal injection of methotrexate. Patients with acute lymphoblastic leukaemia (ALL) may be asymptomatic and develop vision loss (VL). CBMJ 2024 July: vol. 13 no. 02 P: 277-281